ﻣﺘﻔﺮﻗﺎت المخطوط في ﺧﺰاﻧﺔ ﻣﻬني الباروني: دراﺳﺔ تحليلية ﻣﻘﺎرﻧﺔ - الباروني, سناء مهني (الندوة الدولية المخطوطات والكوديكولوجيا: المعارف البينية والافاق البحثية. مهداة إلى الأستاذ الدكتور إبراهيم شبوح, 2026)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba

رﺻﻴﺪ المخطﻮﻃﺎت اﻟﺮياضية بمكتبة ﺟﺎﻣﻊ الباسي بجربة: ﻗﺮاءة تحليلية - اﻟﻬﺎدفي, ﺣﻤﻴﺪة (الندوة الدولية المخطوطات والكوديكولوجيا: المعارف البينية والافاق البحثية. مهداة إلى الأستاذ الدكتور إبراهيم شبوح, 2026)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba

‘We Have Endured’: Islam’s Third Branch Has Deep Roots On This African Island - Addezio, Nadia (Religion Unplugged, 2026)
Wedged between a pizzeria and a clothing shop in Houmt Souk, the capital of Tunisia’s island of Djerba, lies an ancient treasure. The El Barounia Library is one of the oldest centers preserving Ibadi heritage in North Africa. Ibadism presents itself as a third path — between the two major branches —
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba

مشروع الأرشيفات المهددة بالانقراض وإنقاذ مكتبات المخطوطات العائلية بجزيرة جربة: مبادرة محلية ودولية - البوجديدي, علي (التراث المادي (الأثري والمخطوطات) وغرري المادي في ليبيا والدول المجاورة لها الوضعيات المعارصة والآفاق =Patrimoine matériel (archéologique et manuscrit) et immatériel en Libye et dans les pays voisins Situations contemporaines et perspectives, 2025)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Conservation; Manuscrits -- Djerba

التراث المخطوط بجزيرة جربة: صور التنوع الثقافي وعلامة الخصوصية - البوجديدي, علي (تظاهرة التنوع الثقافي مصدرا للتجديد والإبداع, 2025)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba

Modern Ibadi Books on the Move: the “al-Shaykh Mosque” Library in Houmt Souk (Djerba, Tunisia) | رحلات الكتب الإباضية الحديثة: مكتبة “جامع الشيخ” بحومة السوق (جربة، تونس) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2025)
This summer, I have had the chance to return to Djerba (Tunisia) and work with my colleague from Ibadica, Si Mahfoudh Dahman, on documenting part of another library collection there. This month has…
Keywords: Manuscrits -- Djerba; Shaykh, mosquée al- (Houmt Souk, Djerba)

رحلتي إلى جزيرة «جربة» حيث التاريخ والتنوع والعيش المشترك - العبري, بدر بن سالم (المسار, 2025)
Keywords: Manuscrits -- Djerba; Récits de voyage -- Djerba

المخطوطات الطبيّة بالمكتبة البارونية بجربة - الحاجي, بلقاسم (جزيرة جربة عبر التاريخ: من المحليّة إلى العالميّة | L'île de Djerba à travers l'histoire : Du local au mondial, 2025)
"المكتبة البارونية بجربة كما هو محدّد في موقعها على الأنترنت هي: مكتبة عائليّة خاصّة أسّسها أبو عثمان سعيد بن عيسى بن يعقوب الباروني الفسّاطوي . وهو عالم اباضيّ من جبل نفوسة بليبيا، ولد حوالي سنة 1188/ 1775 وتوفّي سنة 1281/1865. يرجع تاريخ تأسيسها إلى سنة 1235/ 1819 عندما استقرّ هذا العالم بجزبرة جربة كمدرّس بالجامع الكبير بعد قضاء عشرين سنة بالقاهرة بين الدّراسة بالجامع الأزهر والتّدريس بوكالة الجاموس وهي وقف الإباضيّة بحي طولون حيث نسخ جلّ المخطوطات. وقد تمت فهرستها بطريقة علميّة بالتّعاون مع مؤسّسة بيت الحكمة والمكتبة الوطنيّة التّونسيّة وتحتوي المكتبة على رصيد هام المخطوطات في مختلف المجلات الفقهية والعلمية وغيرها. نعمل في هذا البحث على تقديم المخطوطات الطبيّة بالمكتبة البارونية حيت نجد عدد هام من المؤلفات الطبيّة في فروع طبيّة عديدة مثل العلاج والأدوية وأجزاء من كتب ومؤلفات شاملة. ومن بين هذه المخطوطات نذك: • التوفيق للطبيب الشقيق بشرح أرجوزة أبي علي حسين بن سينا، مخطوط يتكوّن من 426صفحة. • الجزء الثالث من التذكرة في الطب يتكون من 406 صفحة • آداب المجرات في الطب (مجموعو كتب)، تتكون من 598صفحة. • رسالة في كيفية استعمال الادوية 154صفحة. • غنية اللب في علم الطب 112صفحة"
Keywords: Manuscrits -- Djerba; Médecine -- Djerba

خزانة مخطوطات جامع التّرك بجربة ورحلتها من خلال خوارج النّصوص والوثائق الأرشيفيّة - السلامي, صدق (جزيرة جربة عبر التاريخ: من المحليّة إلى العالميّة | L'île de Djerba à travers l'histoire : Du local au mondial, 2025)
تعرف جربة بكثرة زواياها ومساجدها التي أدّت أدوارا ثقافيّة متعدّدة عبر التاريخ. ومن المعلوم أنّ هذه المؤسسات تحوي خزائن من المخطوطات لاتصالها بوظيفة التّعليم وإقامة طقوس دينيّة من تلاوة القرآن الكريم وقراءة الحديث النبويّ وسرد السيرة ومحافل الذّكر وحلقات التصوّف والاحتفال بالمولد النبويّ الشّريف... ومن هذه المعالم جامع التّرك الذي ارتبط بحضور الجيش الانكشاريّ وتوطّن الأتراك العثمانيّين بجزيرة جربة وبالتالي ارتباطه بالمذهب الحنفيّ. غير أنّ المعلم عرف عبر الأزمنة تغيّرات شملت معماره ووظائفه فبات زمن الاستعمار الفرنسيّ وخاصّة أواخر أربعينات القرن العشرين مقرّا للفرع الزّيتونيّ. وهذه الوظيفة الجديدة تحتاج دعم الجامع بخزانة كتب توفّر مادّة لتلاميذ الفرع المدعوّين إلى مذاكرة برنامج دراسيّ مقرّر لنيل شهادة الأهليّة. ورث جامع التّرك مجموعة من المخطوطات كانت في خزانة زاوية سيدي بوحجر اليزلطيني وهو واضح من خلال خوارج النّصوص. احتاجت الزّاوية ترميما لذا وقع جرد محتويات خزانتها ونقلها لاحقا إلى جامع التّرك. ونستفيد من خلال تتبّع خوارج النصوص التي دوّنت في المخطوطات أنّها تختزل دور عدد من أفراد عائلة بوصرّة الطّرابلسي في تحبيس مخطوطات على زاوية سيدي بوحجر. منها تقييدات تملّك وشراء وولادة وميراث رغم ما اعتراها من مظاهر طمس مختلفة (تسويد، تفحيم، شطب، كشط...). وهي بدورها مكتنزة بمعطيات كوديكولوجيّة لرحلة جمع هذه المخطوطات رافقت مسار أفراد العائلة وعلاقاتَهم التجارية والعلميّة مشرقا ومغربا وانتماءَهم المذهبيّ المالكيّ.
Keywords: Manuscrits -- Djerba; Turuk, mosquée al- (Houmt Souk, Djerba)

Which books has Saʿid al-Shammakhi (d.1883) read? Let him tell you about it. | ما هي الكتب التي قرأها سعيد الشماخي؟ دعه هو يعلمك بها - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2024)
A copy of the Kitāb al-īḍāḥ and accompanying gloss, from the Gouja family library in Djerba, Tunisia. In my recent book, the Ottoman Ibadis of Cairo, I used the library of the Ibadi trade agency, s…
Keywords: Manuscrits -- Djerba

المخطوط الإباضي في مكتبتي العائلة البارونيّة بجربة - تغلات, زهير (جزيرة جربة: التاريخ والإنسان والمجال, 2025)
Keywords: Manuscrits -- Djerba

مكتبة الشيخ مهني الباروني: الرصيد الرقمي المتاح للباحثين - الباروني, سناء مهني (المخطوط والكوديكولوجيا: المعارف البينية واﻵفاق البحثية, 2025)
Keywords: Manuscrits -- Djerba

المخطوط اﻹباضي بالمكتبات العائلية بجربة: نوادر من المخطوطات اﻹباضية - تغلات, زهير (المخطوط والكوديكولوجيا: المعارف البينية واﻵفاق البحثية, 2025)
Keywords: Manuscrits -- Djerba

المكتبات العائلية بجربة ومشروع الرقمنة: مادّة بحثية غزيرة - البوجديدي, علي (المخطوط والكوديكولوجيا: المعارف البينية واﻵفاق البحثية, 2025)
Keywords: Manuscrits -- Djerba

العلامات المائية في دراسة المخطوط العربي - Love Jr, Paul M. (المخطوط والكوديكولوجيا: المعارف البينية واﻵفاق البحثية, 2025)
Keywords: Manuscrits -- Djerba

A Library Lost: The al-Baʿṭūrī Library in Jerba, Tunisia - Love Jr, Paul M. (Social Codicology: The Multiple Lives of Manuscripts in Muslim Societies, 2024)
Abstract In this photo essay, I use the story of a private manuscript library belonging to the al-Baʿṭūrī family in Jerba, Tunisia to reflect on my foray into the world of social codicology and the historical anthropology of rumour surrounding manuscript collections on the island. In some cases, stories about manuscripts in Jerba often have little to do with manuscripts. Instead, they convey information about the people associated with them. In other cases, rumours and stories about manuscripts contain information that is anachronistic, contradictory, or even blatantly untrue. Drawing inspiration from Luise White’s work on vampire narratives in colonial East Africa, I maintain that the rumors about manuscripts and libraries need not contain information that is true in order to convey important information about people and manuscripts in Jerba.
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba

الذكاء الاصطناعي في خدمة التراث المخطوط - الباروني, سعيد بن يوسف (الذكاء الاصطناعي في خدمة التراث المخطوط, 2024)
Keywords: Manuscrits -- Djerba

Tunisie: une communauté musulmane se tourne vers l'IA pour préserver son héritage - AFP (Agence France Presse, 2024)
Dans sa modeste maison de l'île tunisienne de Djerba, Said Al-Barouni s'est donné pour mission, à l'aide des technologies et de l'intelligence artificielle, de préserver l'héritage de sa communauté ibadite, un courant minoritaire et modéré de l'islam. "Regardez ce que l'humidité de...
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba

مشاريع حفظ المخطوطات العائلية بجربة: من الإهمال إلي الرقمنة - البوجديدي, علي (الملتقة الدولي موسى الجمني للتراث الجبالي: آليات الجرد الأثري والتاريخي ووسائله من خلال تجارب مغاربية, 2024)
Keywords: Manuscrits -- Djerba

المخطوط بين التحقيق والتثمين - البوجديدي, علي (الملتقة الدولي موسى الجمني للتراث الجبالي: آليات الجرد الأثري والتاريخي ووسائله من خلال تجارب مغاربية, 2024)
Keywords: Manuscrits -- Djerba

تجارب في توثيق التراث المخطوط بجزيرة جربة 2017-2024 - Love Jr, Paul M. (الملتقة الدولي موسى الجمني للتراث الجبالي: آليات الجرد الأثري والتاريخي ووسائله من خلال تجارب مغاربية, 2024)
Keywords: Manuscrits -- Djerba

مخطوطات جربية في الطب محفوظة بالمكتبة البارونية بجربة - اللواتي, مهدي (ملتقى الجيلاني بن الحاج يحيى لأعلام جربة 2022-05- الدورة الخامسة: 07 = Colloque Jilani Bel Hadj Yahia 5ème Session: 07-05-2022, 2024)
Keywords: Manuscrits -- Djerba

Projets de préservation du patrimoine matériel écrit dans le Jebel Nafusa (Libye) et à Djerba (Tunisie) - Love Jr, Paul M.; Boujdidi, Ali; Mazawi, Ali (Situations contemporaines des patrimoines archéologiques, manuscrits et culturels en Libye et au Maghreb: des richesses à préserver ?, 2023)
Keywords: Bibliothèques -- Djebel Nefousa; Bibliothèques -- Djerba; Manuscrits -- Djebel Nefousa; Manuscrits -- Djerba

الفهرس العام لمخطوطات المكتبة البارونية - الباروني, سعيد بن يوسف (2019)
Keywords: Bibliothèques -- Djerba; Catalogue -- Djerba; Manuscrits -- Djerba

Le catalogue de la bibliothèque al-Bāsī : circulation et thésaurisation du savoir à Djerba - Madani, Sarra (Ecole Pratique des Hautes Etudes, 2019)
Keywords: Basi, mosquée al- (Oualegh, Djerba); Bibliothèques -- Djerba; Manuscrits -- Djerba

“Manuscripts are like vampires” (article in History Compass, 2020) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2021)
A screenshot of my most recent article, “Manuscripts are like vampires” (History Compass, 2020), available online here: I have been super busy with a couple of grant applications for th…
Keywords: Manuscrits -- Djerba

The library of Ibadi historian Saʿīd b. ʿAlī b. Taʿārīt (d.1289/1872) | مكتبة المؤرّخ الإباضي سعيد بن علي بن تعاريت - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
Saʿīd b. ʿAlī b. Taʿārit (d.1289/1872) occupies an important place in the history and historiography of Ibadi communities in the Maghrib as the author of The Epistle on the History of Jerba (Risāla…
Keywords: Manuscrits -- Djerba

The (Almost) Lost Siyar of Jabal Nafusa | سير مشائخ جبل نفوسة (التي كادت تُفقد) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2016)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba; Prosopographie -- Djebel Nefousa

Association pour la sauvegarde de l'île de Djerba (Part 1): Manuscripts | جمعية صيانة جزيرة جربة (الجزء الأول): المخطوطات - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba

Some Observations on Watermarks from the Barouniyya Library | ملاحظات حول العلامات المائية من المكتبة البارونية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba

Bookworms, literally | دود الكتب...فعلا - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Manuscrits -- Djerba

Ibadi Manuscripts in non-Ibadi Libraries | المخطوطات الإباضية بالمكتبات غير الإباضية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
Ibadi libraries, almost without exception, house non-Ibadi books. Sometimes, Ibadi-owned libraries held hundreds of titles by non-Ibadi authors and those titles far outnumbered the Ibadi ones. When…
Keywords: Manuscrits -- Djerba

EAP1216 “The Djerba Libraries Project:” A New Manuscript Digitization Project in Djerba, Tunisia | مكتبات جربة: مشروع جديد لرقمنة المكتبات بجربة (تونس) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
I am delighted to announce the launch of “EAP1216 The Djerba Libraries Project,” a two-year effort to digitize several libraries on the island of Djerba, Tunisia. Funded by Arcadia (a c…
Keywords: Manuscrits -- Conservation; Manuscrits -- Djerba

Preserving Endangered Archives in Jerba, Tunisia: The al-Bāsī Family Library | الحفاظ على الأرشيفات المهدّدة في جربة: مكتبة الباسي العائلية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
The Journal of Manuscript Studies (3:1, Spring 2018) has just published a short research annotation by my colleague Dr. Ali Boujdidi and myself, describing our project on the El Bessi (al-Bāsī) fam…
Keywords: Manuscrits -- Conservation; Manuscrits -- Djerba

Upcoming Public Exhibition for al-Bāsī Library Project in Djerba, Tunisa: معرض مكتبة الباسيين في جربة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
It is my pleasure to announce the upcoming public exhibition of “Conserving Endangered Archives in Jerba: the al-Bāsī Family Library Project” in Djerba, Tunisia, taking place this comin…
Keywords: Manuscrits -- Djerba

Announcing a new manuscript conservation effort in Djerba, Tunisia: the El Bessi Library Project | إعلان بمشروع جديد للحفظ على المخطوطات في جزيرة جربة: مشروع مكتبة جامع الباسي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2017)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Conservation; Manuscrits -- Djerba

‏المخطوطات العائلية في جزيرة جربة التونسية - البوجديدي, علي (مجلة العربي, 2023)
Keywords: Manuscrits -- Djerba

A Library in Fragments: An Inventory of the al-Baʿṭūrī Family & Library in Djerba, Tunisia - Love Jr, Paul M. (Islam on the Margins: Studies in Memory of Michael Bonner, 2023)
Keywords: Bibliothèques -- Djerba; Catalogue -- Djerba; Manuscrits -- Djerba

‏فهرس مخطوطات المكتبة البارونية لمؤسسها الشيخ سعيد بن عيسى الباروني (1188-1281هـ/1775-1865) ‏القسم الاباضي - سيوسيو, صالح بن بكير; بوسنان, محمد بن عمر (المكتبة البارونية, 2018)
Keywords: Bibliothèques -- Djerba; Catalogue -- Djerba; Manuscrits -- Djerba

من تقالد نساخة المخطوطات وتاريخ مجموعة جامع الترك بجربة: مقارنة كوديكولوجية وبينية - السلامي, صدق (ندوة المخطوطات العائلية التونسية: مقارنة كوديكولوجية بدار الكتب الوطنية بتونس, 2022)
Keywords: Manuscrits -- Djerba

دراسة تحليلية مقارنة لأوراق المخطوط المتفرقة في خزانة مهني الباروني - الباروني, سناء مهني (ندوة المخطوطات العائلية التونسية: مقارنة كوديكولوجية بدار الكتب الوطنية بتونس, 2022)
Keywords: Manuscrits -- Djerba

ملح المخطوطات وطرئف النساخ من خلال مجموعات المخطوطات العائلية بجزيرة جربة - البوجديدي, علي (ندوة المخطوطات العائلية التونسية: مقارنة كوديكولوجية بدار الكتب الوطنية بتونس, 2022)
Keywords: Manuscrits -- Djerba

L’Odyssée des manuscrits de la collection al-Bāsī - Madani, Sarra (Manuscrits islamiques : matérialité, usages, traditions comparées Afrique-Moyen-Orient, 2021)
Keywords: Basi, mosquée al- (Oualegh, Djerba); Bibliothèques -- Djerba; Manuscrits -- Djerba

المخطوط بين التحقيق والدراسة - البوجديدي, علي (المخطوط بين التحقيق و الدراسة, 2017)
Keywords: Manuscrits -- Djerba

A long, Centuries-Old Murmuring: Medieval Islamic Manuscripts and their modern Material Histories - Love Jr, Paul M. (The 19th Annual Charles F. Fraker Conference: Thinking with Things: Towards a Matter-Oriented Cultural Analysis, 2013)
Keywords: Manuscrits -- Djerba

مخطوطات عمانية في خزانة سالم بن يعقوب الجربي - العيسري, محمد بن عامر (الذاكرة, 2019)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba

Le donne nei manoscritti berberi - Brugnatelli, Vermondo (2012)
Il secondo brano proposto proviene dal poemetto intitolato Tmaziɣt che fu composto a Jerba (Tunisia) dallo cheikh Šaʿbān b. Aḥmad al-Qannūšī tra la fine del Settecento e gli inizi dell’Ottocento
Keywords: Manuscrits -- Djerba

The Jerba Libraries Project: Digitizing at a Distance and Other Challenges - Love Jr, Paul M. (Les études sur le Maghreb numérique: Ressources en ligne, outils et projets de valorisation, 2021)
Keywords: Manuscrits -- Djerba

Aqwāl Qatāda Makhṭūṭ Ibāḍī Thamīn min Kunūz Jazīrat Jarba - Ibn Thāyir, al-ʿArabī b. ʿAlī (Al-Minhāj, 2011)
Keywords: Manuscrits -- Djerba

Preliminary Catalog of Arabic Manuscripts at the Association pour la Sauvegarde de l’Île de Djerba (Houmet Souk, Tunisia) - Love Jr, Paul M. (2018)
This a preliminary catalog of the Arabic manuscripts held at the Association pour la Sauvegarde de l’Île de Djerba (ASIDJ) on the island of Djerba, Tunisia. These manuscripts (bound volumes and assembled collections of fragments, representing many more titles) are all stored in acid-free boxes or folders. All items are housed in the association’s library in a former zawiya in the city of Houmet Souk. The association also has a sizeable collection of family and other documents in manuscript form that are awaiting cataloging—in case you are interested! Many of the manuscripts carry content related to the history of Ibadism (e.g. MS 013) and the history of Djerba (e.g. MS 01). For example, chronicles or legal compendia containing cases of disputes in Djerba, where there has been a sizeable Ibadi population for centuries.
Keywords: Bibliothèques -- Djerba; Catalogue -- Djerba; Manuscrits -- Djerba

Fihris al-Makhṭūṭāt bi’l-Maktabat al-Bārūniyya - الباروني, سعيد بن يوسف (2000)
Keywords: Bibliothèques -- Djerba; Catalogue -- Djerba; Manuscrits -- Djerba

From Djerba to Warjalān: Manuscript Letters in Private Ibadi Libraries and Their Importance for the Study of Communication among the Maghribi Ibadi Communities - Neji, Mohamed (Journal of Islamic Manuscripts, 2021)
This article focuses on letters in private Ibadi libraries and their importance for understanding the primary means of communication among Ibadi communities in the premodern Maghrib. Using the example of a letter from the 7th/13th-century Ibadi Shaykh Abū ʿAbdallāh al-Ṣidghiyānī from the island of Djerba (Tunisia) to the Ibadis of Warjalān (Algeria), it seeks to highlight the importance of the archive of unedited Ibadi manuscript letters. This corpus of correspondences has not received the care and maintenance it merits because these letters do not belong to a recognized volume or book and are today located in private libraries unavailable to the public. The article also uses the example of al-Ṣidghiyānī’s letter to emphasize the importance of the manuscript letters and their role in maintaining intellectual ties among the Ibadi cities of the Maghrib. This brief article consists of two parts. The first part offers a general presentation of the archive where the letter is today held: the El Barounia Library in Djerba, Tunisia. The second part presents the manuscript and its author in their historical context.
Keywords: Manuscrits -- Djerba

Preserving Endangered Archives in Jerba, Tunisia: The al-Bāsī Family Library Pilot Project - Boujdidi, Ali; Love Jr, Paul M. (Manuscript Studies: A Journal of the Schoenberg Institute for Manuscript Studies, 2018)
Keywords: Manuscrits -- Djerba

Curating Ibāḍī Archives: Notes on the Social Life and Archival Logic of the Bin Yaʿqūb Family Library in Jerba,Tunisia - Love Jr, Paul M. (Local and global Ibadi identities, 2019)
Keywords: Manuscrits -- Djerba

Le manuscrit mathématique de Jerba : Une pratique des symboles algébriques maghrébins en pleine maturité - Abdeljaouad, Mahdi (Ministère de l'Éducation Nationale, Agence Univ. de la Francophonie, 2002)
En partant des travaux de Woepke (1854) qui découvre les symboles algébriques maghrébins à travers un manuscrit d'al-Qalasâdi (m. 1486), des publications de Mohamed Souissi qui, dès 1986, publie plusieurs traités arabes d'algèbre, dans lesquels ces symboles sont couramment utilisés et des recherches d'Ahmed Djebbar, qui dès 1990, repousse de deux siècles la pratique de ces symboles en les découvrant chez ibn al-Yâsamîn et al-Hassâr, nous proposons une synthèse des connaissances actuelles sur les symboles algébriques maghrébins. La description détaillée de ces symboles et la typologie que nous proposons se basent sur un manuscript tardif du XVIIIe siècle, découvert récemment à Djerba (Tunisie), dans la marge duquel une utilisation abondante et systématique de la notation algébrique maghrébine attire l'attention, avec plus de 300 occurences dans des situations différentes.
Keywords: Manuscrits -- Djerba

Aperçu des stratégies des communautés ibadites du Maghreb dans la conservation et la valorisation du patrimoine manuscrit - Mestaoui, Soufien (Horizons maghrébins, 2017)
Keywords: Bibliothèques -- Djerba; Bibliothèques -- Mzab; Manuscrits -- Djerba; Manuscrits -- Mzab